2017
DOI: 10.1063/1.4983066
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of defect formation during heteroepitaxial growth of InGaN alloys on (0001) GaN surfaces

Abstract: We investigate the formation of extended defects during molecular-dynamics (MD) simulations of GaN and InGaN growth on (0001) and ([Formula: see text]) wurtzite-GaN surfaces. The simulated growths are conducted on an atypically large scale by sequentially injecting nearly a million individual vapor-phase atoms towards a fixed GaN surface; we apply time-and-position-dependent boundary constraints that vary the ensemble treatments of the vapor-phase, the near-surface solid-phase, and the bulk-like regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…Furthermore, there are several types of defects such as V-type defects, trench defects and sub-interfacial extended type defects could be appeared due to higher indium content and biaxial compressive strain in the material. But recent studies suggest that V types of defects are mostly kinetically driven, and it cannot be related with higher indium content and with biaxial compressive strain 15,[41][42][43] . On the other hand, it has been suggested that trench types of defects and subinterfacial extended types of defects can be related with higher indium content and as well as with biaxial compressive strain 15,41,42,44 .…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, there are several types of defects such as V-type defects, trench defects and sub-interfacial extended type defects could be appeared due to higher indium content and biaxial compressive strain in the material. But recent studies suggest that V types of defects are mostly kinetically driven, and it cannot be related with higher indium content and with biaxial compressive strain 15,[41][42][43] . On the other hand, it has been suggested that trench types of defects and subinterfacial extended types of defects can be related with higher indium content and as well as with biaxial compressive strain 15,41,42,44 .…”
Section: Resultsmentioning
confidence: 98%
“…It can accurately characterize the elastic, structural and dynamical properties of AlN and GaN, and can well describe the interatomic interaction between Al-Ga. Similar SW potentials have already been successfully applied to investigate InGaN film grown on GaN surface [20,21]. The parameters of Al-Ga-N SW potential are shown in Table 1.…”
Section: Interatomic Potentialmentioning
confidence: 98%
“…(0001) Al-terminated surface substantially improves the surface roughness and crystal quality of deposited AlGaN film. Similarly, J. Gruber et al chose (0001) Ga-terminated GaN template for the growth of InGaN [20]. Ponce et al [40] examined smooth MOCVD films grown on sapphire with a low-temperature GaN buffer layer and reported them to be (0001) Ga-polar.…”
Section: Atomic Migration Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide an effective means to guide experiments to reduce these defects. and [112 ̅ 0] directions respectively [58,59] where the initial substrate, wurtzite, zinc-blende, and defective (i.e., undefinable) regions are shown in black, orange, blue, and white colours respectively. Almost defect-free structures can be grown in the [112 ̅ 0] growth direction (except for the surface which is coloured white), but significant defects (including alteration of wurtzite and zinc-blende regions) exist in the [0001] growth direction.…”
Section: Simulation Application In Additive or Deposition-based Manufacturing Processesmentioning
confidence: 99%